PENGARUH MODEL LATIHAN PHYSICAL ACTIVITY GAMES TERHADAP PENINGKATAN PERCAYA DIRI ATLET PADA CABANG OLAHRAGA KATEGORI OPEN SKILL DAN CLOSED SKILL - Rahmad Fitra, - (2022)
The background of this research is based on the analysis of researchers, athletes in the open skill and closed skill categories are still lacking in self-confidence. The purpose of this study was to determine "the effect of the physical activity games training model on increasing the confidence of athletes in the open skill and closed skill categories of sports ". The research method used is experimental research method using One Group Pre-test Post-test Design . The data collection technique was done by giving a pre-test. Then given treatment with physical activity games training model. Data processing techniques used are Paired Sample T-test and Independent Samples T-test. The population used in this study were athletes from UKM Basketball, UKM Volleyball, UKM Athletics, and UKM Aquatics total of 24 athletes consisting of 14 athletes in the open skill category and 10 athletes in the closed skill category. The research was conducted for 4 weeks with 16 meetings. From research results this show that there is significant influence from the exercise model of physical activity games on increasing self-confidence in athletes in the open skill and closed skill categories, and there are difference enhancement believe self athlete Among branch sport category open skills with closed skills to the training model physical activity games .